Perancangan Strategi Perusahaan Berdasarkan Rasio Finansial pada PT Fajar Surya Wisesa Tbk Sebelum dan Sesudah Munculnya Covid-19 - Tsabitah, Aliva; Chumaidiyah, Endang; Zulbetti, Rita (Universitas Batanghari Jambi, 2024)
This study aims to design strategic recommendations based on financial ratios at PT Fajar Surya Wisesa Tbk before and after Covid-19. This research is motivated by a decline in global paper demand and production as well as a decline in the value of stock prices in the manufacturing sector. Particularly at PT Fajar Surya Wisesa Tbk. In this study, data was collected using the financial reports and stock prices of PT Fajar Surya Wisesa Tbk 12 quarters before the emergence of Covid-19 (April 2017–March 2020) and 12 quarters after the emergence of Covid-19 (April 2020 – March 2023). The data processing method used is the Wilcoxon Signed Ranks Test. The results of the Wilcoxon signed ranks test in the form of 9 financial ratio variables found a significant difference between the values before and after Covid-19. Meanwhile, for the 6 other financial ratio variables and stock prices, there is no significant difference between the values before and after Covid-19. After that, strategic recommendations are given based on test results, and a mapping is carried out on the Strengths and Weaknesses quadrants to get recommendations for strategies that are suitable for the company. In this study the authors provide recommendations on strategies that can be implemented by companies to improve financial performance.